How do private general practitioners manage tuberculosis cases? A survey in eight cities in Indonesia. (December 2015) - Mahendradhata, Yodi; Lestari, Trisasi; Probandari, Ari; Indriarini, Lucia; Burhan, Erlina; Mustikawati, Dyah; Utarini, Adi
Abstract Background Private practitioners (PPs) in high-burden countries often provide substandard tuberculosis (TB) treatment, leading to increased risk of drug resistance and continued transmission. TB case management among PPs in Indonesia has not been investigated in recent years, despite longstanding recognition of inadequate care and substantial investment in several initiatives. This study aimed to assess case management practices of private general practitioners (GPs) in eight major cities across Indonesia. Methods A cross-sectional survey of private GPs was carried out simultaneously in eight cities by trained researchers between August and December 2011. We aimed for a sample size of 627 in total, and took a simple random sample of GPs from the validated local registers of GPs. Informed consent was obtained from participants prior to interview. Diagnostic and treatment practices were evaluated based on compliance with national guidelines. Descriptive statistics are presented. Results Of 608 eligible GPs invited to participate during the study period, 547 (89.9 %) consented and completed the interview. A low proportion of GPs (24.6–74.3 %) had heard of the International Standards for TB care (ISTC) and only 41.2–68.9 % of these GPs had participated in ISTC training. As few as 47.3 % (90 % CI: 37.6–57.0 %) of GPs reported having seen presumptive TB. The median number of cases of presumptive TB seen per month was low (0–5). The proportion of GPs who utilized smear microscopy for diagnosing presumptive adult TB ranged from 62.3 to 84.6 %. In all cities, a substantial proportion of GPs (12.0–45.5 %) prescribed second-line anti-TB drugs for treating new adult TB cases. In nearly all cities, less than half of GPs appointed a treatment observer (13.8–52.0 %). Conclusions The pattern of TB case management practices among private GPs in Indonesia is still not in line with the guidelines, despite longstanding awareness of the issue and considerable trialing of various interventions.